Analisis Sengketa Wanprestasi dan Ganti Rugi dalam Kontrak Pengadaan Jasa Ditinjau dari Kitab Undang-Undang Hukum Perdata - Ladyva Rizqina Dinissa; Susilowati Suparto; Etty Haryati Djukardi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Contract law plays a key role in trade and business. Failure to fulfill obligations in an agreement, known as default, can include non-fulfillment, delays, or performing actions not aligned with the agreement. The aggrieved party is entitled to seek compensation for the default. In a service agreement case resolved through arbitration, the Respondent was found to have defaulted. Despite both parties agreeing to all terms and performing the contract without objection, the Respondent was ordered to pay compensation under Article 1248 of the Civil Code, which includes the concept of